The Goals of Philosophy of Religion: A Reply to Ireneusz Zieminski - Lougheed, Kirk (European journal for philosophy of religion, 2019)
In a recent article, Ireneusz Zieminski (2018) argues that the main goals of philosophy of religion are to (i) define religion; (ii) assess the truth value of religion and; (iii) assess the rationality of a religious way of life. Zieminski shows that each of these goals are difficult, if not impossible, to achieve. Hence, philosophy of religion leads to scepticism. He concludes that the conceptual tools philosophers of religion employ are best suited to study specific religious traditions, rather than religion more broadly construed. But it's unclear whether the goals Zieminski attributes to philosophy of religion are accurate or even necessary for successful inquiry. I argue that an essentialist definition of religion isn't necessary for philosophy of religion and that philosophers of religion already use the conceptual analysis in the way Zieminski suggests that they should. Finally, the epistemic standard Zieminski has in view is often obscure. And when it is clear, it is unrealistically high. Contemporary philosophers of religion rarely, if ever, claim to be offering certainty, or even evidence as strong as that found in the empirical sciences.